Sleep Quality Among a Sample of Medical Students and the Association with Academic Performance: An Updated Data - Abdulrahman Almalki; Moayad Shehata; Khaled Siddiqui; Hamzah Albulushi; Nawaf Alshehri; Ahmed Aldumri; Saeed Alghamdi; Aya Khasati; Siraj Omar Wali; Omar Ayoub (Journal of Epidemiology and Global Health)
Abstract Sleep is influenced by various factors, including social, economic, genetic, and medical factors, and work and study schedules. Medical students are highly susceptible to sleep-related problems. In this study, we aimed to evaluate the sleep patterns and quality of medical students and determine their correlation with academic achievement. This cross-sectional study was conducted at the King Abdulaziz University between November 2022 and April 2023. The participants completed an online questionnaire distributed to all medical students via social media channels. The questionnaire included the Pittsburgh Sleep Quality Index to assess sleep quality and Epworth Sleepiness Scale to measure excessive daytime sleepiness (EDS). Academic performance was self-reported by students based on their grade point average. Of the 274 participants, 54.0% were males with a mean age of 22.81 years. Only 21.5% of students reported normal sleep quality during the previous month, with almost 78.5% reporting poor sleep quality and 40.9% experiencing EDS. Notably, no associations were observed between the sleep quality and sleep–wake patterns and academic performance of the students (p = 0.324 and 0.784, respectively). These findings highlight the substantial prevalence of poor sleep quality and EDS among Saudi medical students, consistent with global trends. Unexpectedly, no significant correlation was observed between sleep quality and student academic performance. These findings suggest that the demanding nature of medical education significantly impacts the sleep patterns and overall well-being of students.